2018
DOI: 10.1029/2017jd027626
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Rivers Carry Nonmonsoon Extreme Precipitation Into Nepal

Abstract: Atmospheric rivers (ARs) are concentrated bands of water vapor that can cause extreme precipitation and severe flooding. Fortunately, due to their 1,500+ km spatial extent, they may also be forecasted days in advance. The goals of this study were to investigate the seasonal climatology of ARs in the Himalayan region of Nepal and to determine the role of ARs in extreme precipitation events. Using the ERA‐Interim atmospheric reanalysis, we applied a standard integrated vapor transport AR detection approach for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…In the Indian coastal regions, Dhana Laskhmi and Satyanarayana (2019; 2020) found that the frequent ARs coming from the westerly jet core regions of the summer monsoon are closely linked to the heavy precipitation events. Moreover, precipitation extremes over the countries near the Bay of Bengal are found to be associated with frequent ARs in the boreal summer (Yang et al ., 2018), especially for the densely populated areas such as Bangladesh, Thailand and Nepal that are highly exposed to hydrological extremes including floods (Rufat et al ., 2015; Periyasamy et al ., 2018; Thapa et al ., 2018) and landslides (Ahmed and Dewan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the Indian coastal regions, Dhana Laskhmi and Satyanarayana (2019; 2020) found that the frequent ARs coming from the westerly jet core regions of the summer monsoon are closely linked to the heavy precipitation events. Moreover, precipitation extremes over the countries near the Bay of Bengal are found to be associated with frequent ARs in the boreal summer (Yang et al ., 2018), especially for the densely populated areas such as Bangladesh, Thailand and Nepal that are highly exposed to hydrological extremes including floods (Rufat et al ., 2015; Periyasamy et al ., 2018; Thapa et al ., 2018) and landslides (Ahmed and Dewan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong orographic lifting and thermal contrasts between the world's largest continent (the Eurasia) and the largest ocean basin (the Pacific), as well as the influence from the world's highest land feature, that is, Tibetan Plateau, the climate system over the EA is extremely complex and distinct, which leads to more challenges in AR identification comparing to other regions, to name a few, distinguishing ARs from strong cyclonic system, quantifying the metrics for ARs with large curvature. In fact, among limited AR studies in the EA, attentions are mainly received by ARs over the northwestern Pacific affecting Japan (Kamae et al, ), Bay of Bengal (BOB), and Arabian Sea (AS) affecting India or Nepal (Thapa et al, ; Yang et al, ). Currently, there is no study focusing on the ARs affecting the Southeast China, especially for the Yangtze River Basin (YRB), where people suffer from flooding almost every summer.…”
Section: Introductionmentioning
confidence: 99%
“…In European countries, the predominant links between precipitation extremes and ARs are found in SON and DJF, with many regions having more than 40% of precipitation extremes caused by ARs (Lavers & Villarini, 2015). On the other hand, in the South Asian monsoon regions, the AR frequency largely occurs during DJF, JJA, and SON, and it also drives precipitation extremes over these regions (Thapa, Endreny, & Ferguson, 2018). Depending on the seasons, the IVT storm track is prominently evident in the North Pacific and Atlantic regions.…”
Section: Resultsmentioning
confidence: 99%